An Assessment of Hatchery Cohort Growth Rates of South African Abalone, Haliotis midae, Across Four Commercial Environments. Issue 5 (13th June 2016) - Vlok, Arnold C.; Difford, Gareth F.; Rhode, Clint; Brink, Danie
Abstract: The abalone, Haliotis midae (commonly referred to as " perlemoen "), is an important aquaculture species in South Africa, accounting for the highest percentage of total aquaculture production revenue. The industry largely makes use of wild, undomesticated broodstock and thus a consortium of top producers was formed to develop a genetic improvement program to increase efficiency and sustainability of the industry. As such, the current study aimed to evaluate growth trait performance (wet weight and shell length) of four hatchery‐derived cohorts of South African abalone, across four differing production environments. No significant cohort‐by‐location effects were found for weight and length traits; however, differences were detected between respective cohorts and locations. It is concluded that a single synthetic population comprised of all hatchery cohorts under a single breeding goal is suitable for production at all test locations. Furthermore, advances in artificial reproductive technologies, genetic markers, and individual identification hold promise for genetic improvement of the species.